Impact of interpatient variability on organ dose estimates according to MIRD schema: Uncertainty and variance‐based sensitivity analysis. Issue 7 (8th June 2018) - Zvereva, Alexandra; Kamp, Florian; Schlattl, Helmut; Zankl, Maria; Parodi, Katia
Abstract : Purpose: Variance‐based sensitivity analysis (SA) is described and applied to the radiation dosimetry model proposed by the Committee on Medical Internal Radiation Dose (MIRD) for the organ‐level absorbed dose calculations in nuclear medicine. The uncertainties in the dose coefficients thus calculated are also evaluated. Methods: A Monte Carlo approach was used to compute first‐order and total‐effect SA indices, which rank the input factors according to their influence on the uncertainty in the output organ doses. These methods were applied to the radiopharmaceutical (S)‐4‐(3‐ 18 F‐fluoropropyl)‐L‐glutamic acid ( 18 F‐FSPG) as an example. Since 18 F‐FSPG has 11 notable source regions, a 22‐dimensional model was considered here, where 11 input factors are the time‐integrated activity coefficients (TIACs) in the source regions and 11 input factors correspond to the sets of the specific absorbed fractions (SAFs) employed in the dose calculation. The SA was restricted to the foregoing 22 input factors. The distributions of the input factors were built based on TIACs of five individuals to whom the radiopharmaceutical 18 F‐FSPG was administered and six anatomical models, representing two reference, two overweight, and two slim individuals. The self‐absorption SAFs were mass‐scaled to correspond to the reference organ masses. Results: The estimated relative uncertainties were in the range 10%–30%, with a minimum and a maximum for absorbed dose coefficients for urinary bladder wall and heart wall, respectively. The applied global variance‐based SA enabled us to identify the input factors that have the highest influence on the uncertainty in the organ doses. With the applied mass‐scaling of the self‐absorption SAFs, these factors included the TIACs for absorbed dose coefficients in the source regions and the SAFs from blood as source region for absorbed dose coefficients in highly vascularized target regions. For some combinations of proximal target and source regions, the corresponding cross‐fire SAFs were found to have an impact. Conclusion: Global variance‐based SA has been for the first time applied to the MIRD schema for internal dose calculation. Our findings suggest that uncertainties in computed organ doses can be substantially reduced by performing an accurate determination of TIACs in the source regions, accompanied by the estimation of individual source region masses along with the usage of an appropriate blood distribution in a patient's body and, in a few cases, the cross‐fire SAFs from proximal source regions.